Oil and the Romanian state - Pearton, Maurice (Oxford : Clarendon Press, 1971)
The book sheds light on the beginnings, political, legal economic and technical of industrialization in Romania.
Includes bibliography and index
kjo 16/01/2019
Loans
Keywords: Petroleum industry and trade; Investments, Foreign